She is charged 25 dollar interest per year so 125 dollars in 5 years. Then she has to pay back 625 dollars.
Answer:
x= -7
Step-by-step explanation:
1/2(4-6x)=23
Take1/2 of the numbers in the (). It will be 2-3x.
2-3x=23 subtract 2 from both sides to get x by itself
-3x=21 now divide the 21 by -3
x= -7
Answer:
Step-by-step explanation:
(2n+ 2)(6n+ 1)
2n+6n=8n
1+2=3
=8n+3
The first thing we are going to do in this case is to rewrite the expression.
We have then:
x ^ 3 + 4x ^ 2 + x - 6
Factoring the expression we have:
(x-1) * (x + 2) * (x + 3)
Therefore, we observe that the following binomial is a common factor:
(x + 2)
Answer:
B. x plus 2